2006
DOI: 10.3354/ame045107
|View full text |Cite
|
Sign up to set email alerts
|

SAR11 dominance among metabolically active low nucleic acid bacterioplankton in surface waters along an Atlantic meridional transect

Abstract: Low nucleic acid (LNA) bacterioplankton (sorted by flow cytometry) were characterised in surface water samples along a meridional transect from 48°N to 40°S across the Atlantic Ocean. The LNA bacterioplankton abundance and metabolic activity, assessed by their 35 S-methionine uptake rate, were similar along the transect, representing 36 ± 6 and 36 ± 11% of total bacterioplankton, respectively. Fluorescence in situ hybridisation analysis of the flow-sorted cells revealed that the LNA bacterioplankton population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
90
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 30 publications
21
90
2
Order By: Relevance
“…Abundance The high relative abundance of SAR11 cells we report for the BATS site is consistent with previous studies in the Sargasso Sea (Morris et al, 2002;Malmstrom et al, 2004), the eastern North Atlantic subtropical gyre (Mary et al, 2006) and the coastal oligotrophic Mediterranean Sea (Alonso-Saez et al, 2007). The ubiquity and numerical dominance of SAR11, supported by genomic and culture evidence revealing their metabolism Giovannoni et al, 2005a) and cell-specific radioactive substrate uptake experiments (Malmstrom et al, 2004;Mou et al, 2007) is compelling evidence that these cells play a major role in the oxidation of organic carbon in the oceans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Abundance The high relative abundance of SAR11 cells we report for the BATS site is consistent with previous studies in the Sargasso Sea (Morris et al, 2002;Malmstrom et al, 2004), the eastern North Atlantic subtropical gyre (Mary et al, 2006) and the coastal oligotrophic Mediterranean Sea (Alonso-Saez et al, 2007). The ubiquity and numerical dominance of SAR11, supported by genomic and culture evidence revealing their metabolism Giovannoni et al, 2005a) and cell-specific radioactive substrate uptake experiments (Malmstrom et al, 2004;Mou et al, 2007) is compelling evidence that these cells play a major role in the oxidation of organic carbon in the oceans.…”
Section: Discussionsupporting
confidence: 92%
“…These organisms have the smallest genomes known for free-living heterotrophic cells, an apparent consequence of genome streamlining and reduction driven by the selection for efficient growth in oligotrophic ocean habitats (Giovannoni et al, 2005a). Mary et al (2006) found that SAR11 dominated the low nucleic acid fraction of bacterioplankton in the North Atlantic subtropical gyre, consistent with the prediction that small genomes are common to this clade.…”
Section: Geochemical Patterns At Bats and Sar11 Metabolismsupporting
confidence: 67%
“…This progressive reduction in diversity could be related to the increase found in one Alphaproteobacteria family (i.e., the Rhodobacteraceae, increasing from 3% relative abundance at time 0 to 485% at day 8), at the expense of the Gammaproteobacteria, Cyanobacteria and SAR11 clade members. Several authors have found that SAR11 clade bacteria are large contributors to the LNA cells fraction in ocean environments (Fuchs et al, 2005;Longnecker et al, 2005;Mary et al, 2006;Vila-Costa et al, 2012). This is in agreement with the parallel reduction found in the number of LNA cells and in the relative abundance of SAR11 during the experiment.…”
Section: Discussionsupporting
confidence: 84%
“…However, no PCR cloning was used in this study, and the percentage hits to SAR11 from the sequencing of random fragments were similar to those enumerated using fluorescent in situ hybridization in surface water in other studies (Mary et al, 2006). It is clear that large fragment-length inserts of fosmid libraries confer a Figure 3 Fragment recruitment plots for key bacterioplankton species.…”
Section: Resultssupporting
confidence: 60%
“…(Suzuki et al, 1997;Buchan et al, 2005). In contrast to an estimated 25% abundance of SAR11 in marine microbial communities from plasmid libraries (Giovannoni et al, 2005) and 12-37% abundance from direct counting of SAR11 using fluorescent in situ hybridization (Mary et al, 2006), Gilbert et al (2008) isolated only a single clone containing a 16S rRNA gene with homology to the SAR11 clade from a marine surface water fosmid library of 10 000 clones. It is interesting that this clone consisted largely of the 48-kb hypervariable region neighbouring the 16S rRNA gene, with a richer GC content than the GC-poor SAR11 core genome.…”
Section: Introductionmentioning
confidence: 99%